Hubungan Kompetensi, Pelatihan Dan Pendidikan Dengan Kinerja Bidan - Silvia Ningsih; Wintarsih Wintarsih (Jurnal Keperawatan Muhammadiyah, 2022)
Background: Midwives are the spearhead in providing maternal and child services. Midwives' performance is influenced by internal and external factors, some of which are competence, training and education. UPTD Jayanti Public Health Center, Tangerang Regency, in general, midwives have attended various trainings, in fact there are still many midwives who have not received training according to their current duties. It was also found that most of the midwives had a D3 education. Objective: To determine the relationship between competence, training and education with the performance of midwives at the Jayanti Public Health Center, Tangerang Regency in 2022. Methodology: This research is a quantitative analytic study using a cross sectional design. The sample in this study was a midwife who served at the Jayanti Public Health Center, Tangerang Regency as many as 45 respondents with a total sampling technique. Data were analyzed using Chi Square test with 95% confidence level (Î± = 0.05). Results: The results of the univariate analysis revealed that most of the midwives with good performance were 71.1%, high competence was 66.7%, appropriate training was 68.9%, and D3 education was 66.7%. The results of the bivariate analysis obtained competence with p = 0.000 < 0.005, training 0.014 < 0.005 and education 0.048 < 0.005. Conclusions and Suggestions: there is a significant relationship between competence, training and education with the performance of midwives. It is hoped that in the future midwives can continue to motivate themselves in improving knowledge in the field of midwifery, carry out every task as a midwife well, and openly accept input from the supervision carried out by the MCH coordinating midwife